Novel Trialkoxy-Substituted Onium Salts as Highly Sensitive and Stable Photoinitiators Reactive to IR Laser - Kunita, Kazuto; Ooshima, Yasuhito; Oohashi, Hidekazu (Journal of Photopolymer Science and Technology, 2014)
New series of diazonium salts and iodonium salts, which show practical level of sensitivity and stability as an IR sensitive photoinitiator for CTP plates, are developed. We investigated the substituent effect on the pheny group adjacent to diazonium or iodonium group. The results show 2,4,6-trialkoxy substituted phenyl group can beautifully balance sensitivity, thermal stability and light stability for both series of initiators. These new onium salts made it possible to create CTP plates that are processible without darkroom conditions.